Perancangan dan Implementasi Data Warehouse Penjualan (Studi Kasus: Northwind Sample Database) - Ardiyanti, Ni Putu Novia; Zulkarnain, Muhammad Firdaus; Sandi, I Wayan Wijaya Kusuma; Hendrawan, I Dewa Ngurah Tri; Mahendra, Ida Bagus Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2021)
Complex analysis is essential for corporate decision-making. The data warehouse is considered more effective to support the analysis process, design, and business decision-making. Usually, a company will build a data warehouse to store operational data that is useful in the business analysis process, so the information that the company wants can be prevalent more easily. The study will arrange a design and implementation of the data warehouse, which uses the Northwind database as its source. For the warehouse data storage, a nine-step design technique and the purification software are used to implementing the process. The design and implementation will form a sales fact chart containing information that use to help the company's business analyses and decisions, which in this study is visualized using a Microsoft Power Business Intelligence application.